Efficacy of removal of calcium hydroxide medicament from root canals by endoactivator and endovac irrigation techniques: A Systematic review of in vitro studies - Margi Parikh; Karkala Venkappa Kishan; Nidhi P Solanki; Maitry Parikh; Krushn Savaliya; Vinukonda Hima Bindu; T Das Devika (Wolters Kluwer Medknow Publications, 2019)
Introduction: The aim of this systematic review was to systematically evaluate and summarize the outcomes of in vitro studies comparing Endoactivator irrigation and Endovac irrigation techniques for removing calcium hydroxide (Ca[OH]2) medicament from the root canals. Materials and Methods: The research question was developed according to the population, intervention, comparison, and outcome strategy. A computerized literature search was conducted in Medline, PubMed, Google Scholar, and Embase. A hand search of the reference lists of identified articles was performed to separate relevant articles. Two reviewers critically assessed the studies that fulfilled the inclusion criteria and processed. Evaluation of the risk of bias of the studies was performed independently by the two reviewers. Results: After study selection, 61 were assessed for eligibility. Of these, 13 met the inclusion criteria and were included in the systematic review. Since significant heterogeneity was found in the methodologies, it was not possible to conduct a meta-analysis. Conclusions: On the basis of available evidence, we determined that Endoactivator irrigation technique showed better performance in removing Ca(OH)2intracanal medicaments from middle third and coronal third area of the root canals and Endovac irrigation technique showed better performance from the apical third area of the root canals. Due to the limitations, small sample sizes, and low number of included studies, further research is needed to confirm our results.